The Influence of Internal Communication and Work Discipline on Employee - Suwanto Suwanto (Universitas Negeri Makassar, 2020)
This study empirically tests whether internal communication and work discipline are applied to realize employee performance at PT. Duta Putra Sejahtera, Jakarta. This study uses a qualitative descriptive method with data collection techniques, namely observation, and distribution of questionnaires/questionnaires. The data analysis techniques used were validity and reliability tests, classic assumption tests (normality test, heteroscedasticity, and multicollinearity tests) along with multiple linear regression analysis, and simple linear regression analysis that was processed using SPSS 20. Sixty-five respondents using the saturated sample method. Internal communication significantly affects employee performance with a significant figure of 0.000 <0.05 and t count 11.911> t table 1.669. Work discipline significantly affects employee performance with a significant number of 0.751 <0.05 and t count -0.319> t table 1.669. The effect of Internal Communication (X1) and Work Discipline (X2) on Employee Performance (Y) has a significant effect simultaneously. It can be seen that the f count is with a significant level of 0.000 <0.05, then the degree of freedom (df) is (k-1) or the degree of the numerator and (NK) for the degree of denominator where n = number of observations and k = the number of variables, the obtained F table is 3.99 so that the value of f count is greater than the table (242.696> 3.99). Thus the test results show that Ho is rejected and Ha is accepted. It indicates that together (simultaneously), the independent variables (internal communication and work discipline) have a significant effect on the dependent variable (performance).